Study on the noise reduction effect of sound barriers on the aerodynamic noise of high-speed trains - Zhang, Rui; Li, Hui; Yang, Junquan; Chen, Xiaoxiong; Yang, Shengyou (Frontiers in Acoustics, 2025)
In recent years, the continuous increase in the speed of high-speed trains has led to growing concern about noise generated by train operations. Currently, three types of sound barriers are commonly used: fully enclosed, semi-enclosed, and vertical. The effectiveness of noise reduction due to complex aerodynamics in higher-speed trains remains unclear and requires further research. This article employs ANSYS Fluent fluid software to establish a full-scale three-dimensional numerical model that simulates the wind tunnel test of a train traveling at a speed of 350 km/h. The noise distribution in the section with the largest noise source is analyzed in COMSOL using the method of line sound source comparison. Additionally, we investigate the noise reduction efficiency of various types and sealing degrees of sound barriers concerning aerodynamic noise. The results indicate that the fully enclosed sound barrier provides the best noise reduction across all frequency ranges, followed by the vertical sound barrier, which offers the second-best noise reduction effect. For high-frequency noise, a higher sealing degree of the sound barrier correlates with improved noise reduction. In highly sensitive areas, priority should be given to fully enclosed sound barriers, followed by vertical sound barriers.